2011
DOI: 10.1590/s1516-35982011000200024
|View full text |Cite
|
Sign up to set email alerts
|

Características de carcaça de caprinos de cinco grupos raciais criados em confinamento

Abstract: RESUMO -Este trabalho foi realizado com o objetivo de avaliar a influência do grupo racial e da condição sexual nas características da carcaça de caprinos jovens criados em confinamento. Foram utilizados 91 animais, 52 machos e 39 fêmeas, pertencentes a cinco grupos raciais: Alpino, ½Boer + ½Alpino, ½Anglo Nubiano + ½Alpino, ¾Boer + ¼Alpino, e ½Anglo Nubiano + ¼Boer + ¼Alpino. Foi tomado o peso ao jejum, no dia do abate, após 24 horas de jejum de sólidos. Foram tomadas medidas biométricas e de carcaça, objetiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
3
10
0
2
Order By: Relevance
“…The crossbred goats had lower measurements the higher the use of Boer breed. These results are consistent with Menezes (2008) and Gomes et al (2011), who verified influence of breed group on internal and external carcass length and leg length, and Alpine showed longer carcasses than crossbred Boer goats. According to Dhanda et al (1999), Alpine goats have a taller and longilineal body structure, possibly because they are dairy animals.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The crossbred goats had lower measurements the higher the use of Boer breed. These results are consistent with Menezes (2008) and Gomes et al (2011), who verified influence of breed group on internal and external carcass length and leg length, and Alpine showed longer carcasses than crossbred Boer goats. According to Dhanda et al (1999), Alpine goats have a taller and longilineal body structure, possibly because they are dairy animals.…”
Section: Resultssupporting
confidence: 92%
“…In accordance with this statement, it can be concluded that the average amount of fat cover observed in this study is considered reasonable but higher than the values reported by Menezes (2008) and Gomes et al (2011), which may be explained by the higher slaughter weight of the kid goats in this study. The best results achieved by the crossbred kids can be explained by the increased tissue deposition per unit of carcass length in this group, which is a characteristic of great interest in obtaining higher quality carcasses.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Menezes et al (2012) avaliando o ganho de peso e medidas biométricas de caprinos jovens, encontraram médias para EC superiores para machos (3,1) em relação às fêmeas (2,9), assim como neste trabalho. No entanto, Gomes et al (2011) ao estudarem a zoometria de caprinos de cinco grupos raciais (Alpino, ½ Boer + ½ Alpino, ½ Anglo Nubiano + ½ Alpino, ¾ Boer + ¼ Alpino, e ½ Anglo Nubiano + ¼ Boer + ¼ Alpino) criados em confinamento, observaram médias opostas para o EC, onde as fêmeas obtiveram maiores escores (3,1) que os machos (2,9). Um bom EC pode representar vantagem para o produtor, principalmente se os cabritos foram vendidos vivos para o abate, como é rotina em alguns criatórios.…”
Section: Resultsunclassified